ADENOID CYSTİC CARCINOMA TREATED WITH ELECTROCAUTERY– 5-YEAR SURVIVAL - Arben Rexhepi; Marija Zdraveska; Dejan Todevski; Aleksandra Tatabitovska; Irfan Ismaili; Deska Dimitrievska; Tome Stefanovski; Sasho Banev; Michael Simoff (Македонско лекарско друштво = Macedonian Medical Association, 2020)
Adenoid cystic carcinoma (ACC) is an uncommon neoplasm which arises from the major and minor salivary glands of the head and neck. Rarely, it can develop from secretory glands originating in the trachea, breast, lacrimal glands or other exocrine glands. We present a case of a fifty-years-old female patient with a polypoid adenoid ACC, growing from the middle of the left main bronchus causing obstruction of the bronchial lumen. Complete resection of the polypoid mass was accomplished using an electrocautery snare through the flexible bronchoscope, cauterizing the stalk in one attempt. The tumor was extracted in the manner of foreign body extraction, attaining complete recanalization and providing patency of the visible bronchial tree with no immediate or late complications. The followup bronchoscopy after 6 months found no signs of persistent or recurrent disease. The patient was followed at 6 and 12 months and every year for 5 years and no signs for local recidive or metastasis was found. We recommend considering endoscopic electrocautery for selected endobronchial or endotracheal cases of ACC, where surgical or oncologic treatment is not possible, in curative or palliative purposes.
ТРЕТМАН НА АДЕНОИДЕН ЦИСТИЧЕН КАРЦИНОМ СО ЕЛЕКТРОКАУТЕР- 5-ГОДИШНО ПРЕЖИВУВАЊЕ
Keywords: adenoid cystic carcinoma; endobronchial electrocautery; resection